Sistem Pendukung Keputusan Pemilihan Perumahan Terbaik di Kota Garut - Muhammad Yasir; Mahdiyana; Muhamad Zein Akbar; Khantaqwa Amri; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
With many apartment sponsors, it is not easy for interested parties to decide on an apartment that meets their criteria requirements. Choosing housing can be based on criteria, including a healthy, comfortable home, and residents feel safe. The author compiles data with five perum residences in the city of Garut, namely Aulia residence, Ghani Cinunuk Indah, Griya Telaga Bodas, Griya Wanamekar and Asri Cibatu. The goal is to create a decision support system (DSP) to help buyers in choosing an apartment. The author uses the technical methods (SAW), (WP), and (TOPSIS), to compare which calculation is the best.